2013
DOI: 10.1080/10871209.2013.789938
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Catch Orientation Among Minnesota Walleye, Northern Pike, and Bass Anglers

Abstract: We compared the catch orientations of Minnesota walleye (Sander vitreus), northern pike (Esox lucius), largemouth bass (Micropterus salmoides), and smallmouth bass (Micropterus dolomieu) anglers. Results were derived from 2009, 2010, and 2012 surveys of anglers targeting these different species. Consistent with previous research, we identified four dimensions of anglers' catch orientation: (a) catching something, (b) catching big fish, (c) catching many fish, and (d) keeping fish. Walleye anglers were the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 30 publications
1
23
1
Order By: Relevance
“…We found some support for protected slot limits among Northern Pike anglers in our study, and prior research has suggested that Northern Pike anglers who place greater importance on catching large fish are more supportive of restrictive regulations (Schroeder and Fulton 2013); however, our results indicate that people generally still prefer to fish at lakes without protective slot limits. Further research is needed to clarify anglers' knowledge of how protected slot limits can influence fish population characteristics in a lake.…”
Section: Conclusion Management Implications and Future Researchcontrasting
confidence: 63%
See 3 more Smart Citations
“…We found some support for protected slot limits among Northern Pike anglers in our study, and prior research has suggested that Northern Pike anglers who place greater importance on catching large fish are more supportive of restrictive regulations (Schroeder and Fulton 2013); however, our results indicate that people generally still prefer to fish at lakes without protective slot limits. Further research is needed to clarify anglers' knowledge of how protected slot limits can influence fish population characteristics in a lake.…”
Section: Conclusion Management Implications and Future Researchcontrasting
confidence: 63%
“…Regulations strongly affected site choice preferences, particularly for spearers. Catch-related attitudes have been found to be related to the fish species targeted (Sutton 2003;Schroeder and Fulton 2013), and our results indicated that these attitudes may also be related to fishing method. Individuals participating in dark house Downloaded by [Lycoming College] at 20:22 01 December 2014 spearing reported weaker attitudes toward catching some or many Northern Pike than did anglers.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…While these and other studies have furthered our knowledge of mode effects' impact on the distribution of participants' sociodemographic characteristics, they do not, for the most part, address the potential impact mode effects may have on variables of more substantive interest to recreational fisheries managers. For example, indicators of anglers' harvest orientations and catch rates have potential implications for setting bag limits for specific species (Schroeder and Fulton 2013). An understanding of angler fishing-related expenditures can also reveal the economic impact and value that recreational fisheries have to communities and the state (Southwick Associates 2013).…”
Section: Survey Methods and Evaluation In Human Dimensions Researchmentioning
confidence: 99%